Normative Data for the D-KEFS Color-Word Interference and Trail Making Tests Adapted in Greek Adult Population 20–49 Years Old - Marianna Tsatali; Fotini Surdu; Andromachi Konstantinou; Despina Moraitou (NeuroSci)
Background: This study was designed to adapt the Delis–Kaplan Executive System (D-KEFS) version of the Color-Word Interference (CWIT) and Trail Making Tests (TMTs) for the Greek adult population from 20 to 49 years old, since it is of research as well as clinical importance to detect executive functions’ impairment in young adults with neurological or/and psychiatric conditions. Aims: Norms for the Greek adult population have been calculated to be available for neuropsychologists and health professionals who work in relevant settings. Methods: The study sample consisted of 101 healthy adults (41% male and 60% female) aged 20 to 49 years (M = 32.16, SD = 11.57) with education from 12 to 19 years of schooling (M = 14.51, SD = 0.89). A Pearson correlation test as well as a chi square test were conducted to examine potential associations between gender, age, education, and participants’ performance. Afterwards, we calculated normative data using raw scores and transformed them into percentile scores. Finally, Greek norms were compared to the original raw scores, which were transformed into scaled scores by Delis et al. (2001). Results: The findings showed that age was the only variable which affected CWIT, whereas level of education as well as age were predictive factors for most TMT conditions, except for the visual scanning test (Condition 1). Gender did not affect both tests. Finally, D-KEFS norms for CWIT and TMT are available for the Greek adult population to help clinicians detect executive functions’ deficits and therefore adjust tailored therapeutic strategies. Additionally, it is of great importance to use these tests for research purposes. Conclusion: Given that executive functions are assumed as high-level skills, which are highly related to everyday functionality, adapted tests contribute not only to assess the progression of any existing neurological as well as psychiatric disorders, but they can also be used to evaluate patients’ ability to live independently, as well as their access to work.